MC68000 Microprocessor stand alone educational board - Heng, Poh Xuan (2012)
The Motorola 68000 is a 16/32-bit CISC microprocessor core designed and it has become a learning tool in most universities in the world due to its simplicity, flexibility, and performance. It is the first member of the successful 32-bit M68k family of microprocessors and was introduced in 1979. It is generally software forward compatible with the rest of the line despite being limited to a 16-bit wide external bus. The aim of the project is to design a stand-alone MC68000 development board that can be used in education and short courses. The system is equipped with several input/output devices such as keypad, LED, LCD, DIP switch, 7-segment display, dot matrix, DC motor, multi-segment display and traffic light display. In addition, the system has built-in programming code for user to test the system functionality. In order to train the user, the system also allows the user to keyin the code manually into the system to test its I/O device.